2023
DOI: 10.3389/fimmu.2023.1268916
|View full text |Cite
|
Sign up to set email alerts
|

ER stress mediates Angiotensin II-augmented innate immunity memory and facilitates distinct susceptibilities of thoracic from abdominal aorta to aneurysm development

Yifan Lu,
Yu Sun,
Fatma Saaoud
et al.

Abstract: To determine the roles of endoplasmic reticulum (ER) stress and trained immunity, we performed transcriptome analyses on the thoracic aorta (TA) and abdominal aorta (AA) from the angiotensin II (Ang II)-HFD-ApoE-KO aneurysm model and made significant findings: 1) Ang II bypassed HFD-induced metabolic reprogramming and induced stronger inflammation in AA than in TA; 2) Ang II and HFD upregulated 890 genes in AA versus TA and induced cytokine signaling; 3) Ang II AA and TA upregulated 73 and 68 cytokines, scRNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…Each of these trained immunity types is characterized by specific mechanisms, including acetyl-CoA-cholesterol-driven histone acetylation dependence, S-adenosylhomocysteine (SAH) hypomethylationtriggered histone demethylation dependence, and glycolysisindependent metabolic pathways (2). These concurrent forms of trained immunity collectively play a pivotal role in exacerbating inflammation (13)(14)(15)(16)(17)(18)(19)(20) and driving the progression of atherosclerosis (2,21). In addition, this paper clearly showed that metabolomic reprogramming exhibits pronounced specificity at the tissue and subcellular organelle levels (22,23).…”
Section: Introductionmentioning
confidence: 77%
“…Each of these trained immunity types is characterized by specific mechanisms, including acetyl-CoA-cholesterol-driven histone acetylation dependence, S-adenosylhomocysteine (SAH) hypomethylationtriggered histone demethylation dependence, and glycolysisindependent metabolic pathways (2). These concurrent forms of trained immunity collectively play a pivotal role in exacerbating inflammation (13)(14)(15)(16)(17)(18)(19)(20) and driving the progression of atherosclerosis (2,21). In addition, this paper clearly showed that metabolomic reprogramming exhibits pronounced specificity at the tissue and subcellular organelle levels (22,23).…”
Section: Introductionmentioning
confidence: 77%
“…But two recent animal studies and data analyses of animal studies provide at least evidence that TI could also be involved in the development and progression of aortic aneurysms [75,76]. One study found that ER stress and TI might play a role for thoracic or abdominal aortic aneurysms [75].…”
Section: Abdominal Aortic Aneurysmsmentioning
confidence: 99%
“…But two recent animal studies and data analyses of animal studies provide at least evidence that TI could also be involved in the development and progression of aortic aneurysms [75,76]. One study found that ER stress and TI might play a role for thoracic or abdominal aortic aneurysms [75]. For this, the authors utilized 9-10 weeks old apolipoprotein E-deficient (ApoE-/-) mice that were treated with angiotensin II (AngII, 1000 ng/kg/min) via aortic minipumps and in parallel fed with a HFD (2% cholesterol and 20% fat) for 28 days to foster the development of aortic aneurysms.…”
Section: Abdominal Aortic Aneurysmsmentioning
confidence: 99%
“…Pathological findings indicated that AAAs have the features of vascular remodeling and the loss of VSMCs ( 30 ). Despite many progresses in determining the roles of genetic risk factors ( 31 ), inflammatory stimuli, inflammasome activation and pyroptosis ( 32 , 33 ), monocytes and macrophages ( 17 , 34 ), Tregs ( 35 ), cell death ( 36 ), reactive oxygen species (ROS) ( 37 39 ), matrix metalloproteinases (MMPs), microRNAs, circular RNAs ( 40 ) and epigenetics ( 38 ), VSMC phenotypic switching ( 13 ) and calcification ( 41 ), advanced technologies for gene discovery ( 31 ), and animal models ( 42 , 43 ), a significant question remains: which innate immune mechanisms are underlying the inflammatory signal amplification for the localized dilatations that happened in specific areas of the aorta ( 42 ).…”
Section: Introductionmentioning
confidence: 99%